Pengaruh Brand Image, Kualitas Produk Dan Persepsi Harga Terhadap Kepuasan Konsumen Starbucks Puri Surya Jaya Sidoarjo - Resti Wanda Lian Putri; Mataji (Cahaya Ilmu Bangsa, 2025)
For some people, drinking coffee at certain cafes is considered a symbol of social status or a modern lifestyle. Many people consider drinking coffee as a way to socialize, work, or simply enjoy leisure time. Starbucks itself provides a wide selection of drinks, from coffee to specialty drinks that are constantly being updated. In addition, there is also a selection of snacks and heavy meals that can be enjoyed. This type of research uses quantitative research with Non-Probability Sampling with Accidental Sampling Technique. The population in this study were 100 respondents of Starbucks Puri Surya Jaya Sidoarjo consumers who were obtained from filling out questionnaires via google form with Likert scale calculations. The results of this study indicate that Brand Image (X1) has a positive and significant effect on Consumer Satisfaction (Y), Product Quality (X2) has a positive and significant effect on Consumer Satisfaction (Y), Price Perception (X3) has a positive and significant effect on Consumer Satisfaction (Y), Brand Image, Product Quality, and Price Perception simultaneously have a positive and significant effect on Consumer Satisfaction (Y). Keywords: Brand Image, Product Quality, Price Perception, Consumer Satisfaction